1997
DOI: 10.1159/000201478
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophils in Cerulein-Induced Pancreatitis in Rats: Possible Involvement of Apoptosis

Abstract: We investigated the role of neutrophils and the involvement of apoptosis in cerulein-induced acute pancreatitis. Male Sprague-Dawley rats were divided into 2 groups. In the control group, acute pancreatitis was induced by subcutaneous injections of cerulein. In methotrexate-treated group, the rats received intraperitoneal injections of methotrexate to produce neutrophil depletion before the injections of cerulein. The rats were sacrificed at the indicated time points until 72 h after the first injection of cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 26 publications
3
20
0
Order By: Relevance
“…Sandoval et al [47] have reported a dramatic increase in apoptotic acinar cells by administration of antineutrophil serum, which, comparable to aICAM-1 (an intercellular adhesion molecule-1, neutralizing antibody), signifi cantly reduced the extent of necrosis and infl ammatory infi ltrate. Similar results were observed in another study wherein treatment with methotrexate resulted in a signifi cant depletion of neutrophils as shown by low myeloperoxidase levels and a consecutive increase in apoptotic acinar cell death [48] . Yet another study, using taurocholate-induced severe acute pancreatitis as the experimental model, showed that neutrophils, via a TNF-␣ -dependent mechanism, may be involved in the development of apoptotic as well as necrotic forms of acinar cell death [49] .…”
Section: Neutrophils and Apoptosissupporting
confidence: 85%
“…Sandoval et al [47] have reported a dramatic increase in apoptotic acinar cells by administration of antineutrophil serum, which, comparable to aICAM-1 (an intercellular adhesion molecule-1, neutralizing antibody), signifi cantly reduced the extent of necrosis and infl ammatory infi ltrate. Similar results were observed in another study wherein treatment with methotrexate resulted in a signifi cant depletion of neutrophils as shown by low myeloperoxidase levels and a consecutive increase in apoptotic acinar cell death [48] . Yet another study, using taurocholate-induced severe acute pancreatitis as the experimental model, showed that neutrophils, via a TNF-␣ -dependent mechanism, may be involved in the development of apoptotic as well as necrotic forms of acinar cell death [49] .…”
Section: Neutrophils and Apoptosissupporting
confidence: 85%
“…The involvement of apoptosis and necrosis in pancreatic acinar cells in rat models of experimental pancreatitis, such as pancreatic duct ligation, ethionine-induced pancreatitis, and cerulein-induced pancreatitis, has been shown by many investigators [27][28][29][30][31]. Neutrophil depletion in cerulein-induced pancreatitis leads to amelioration of pancreatic injury during the early stage, and enhancement of apoptosis by neutrophil depletion occurs during the late stage [31].…”
Section: Nf-îb In Experimental Models Of Acute Pancreatitismentioning
confidence: 98%
“…Neutrophil depletion in cerulein-induced pancreatitis leads to amelioration of pancreatic injury during the early stage, and enhancement of apoptosis by neutrophil depletion occurs during the late stage [31]. Development of apoptosis may be negatively correlated with the severity of pancreatitis [31].…”
Section: Nf-îb In Experimental Models Of Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Am. than in non-cancerous regions of the liver, suggesting an In the present study, we determined the PLA 2 levels in non- damage (31,32). In the present study, neutrophils were noted cancer, but the role infiltrating inflammatory cells in biliary…”
mentioning
confidence: 62%